The daughters break the rules - Philbin, Joanna (New York : Little, Brown, 2010)
When New York City fourteen-year-old Corina impulsively reveals incriminating information about her multi-billionaire father, he replaces her unlimited funds with an antiquated cell phone, a Metrocard, and a twenty-dollar weekly allowance.
Kirkus Review
Kirkus Review, October 2010
Young Adult.
Young Adult
Keywords: Fathers and daughters -- Juvenile fiction; Friendship -- Juvenile fiction; High schools -- Juvenile fiction; Schools -- Juvenile fiction; Single-parent families -- Juvenile fiction; Wealth -- Juvenile fiction; Fathers and daughters -- Fiction; Friendship -- Fiction; High schools -- Fiction; Schools -- Fiction; Single-parent families -- Fiction; Wealth -- Fiction; Father-daughter relationship -- Fiction; Friendship -- Fiction; High schools -- Fiction; School stories; Single-parent families -- Fiction; Wealth -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction